Sociological consciousness: a concept analysis and implications for occupational therapy/ Consciência sociológica: uma analise conceitual e implicações para terapia ocupacional - Kyler, Darby; Taff, Steven (Cadernos Brasileiros de Terapia Ocupacional, 2020)
This article explores sociological consciousness, a framework of thought proposed by Peter Berger, and its potential value for occupational therapy. This article explores how Berger’s four motifs (debunking, unrespectable, relativization, and cosmopolitan) of sociological consciousness can be taught as a process to help occupational therapists frame their thinking when approaching various clients and situations. The current study answers three questions: “What is sociological consciousness?”, “Is sociological consciousness valuable?”, and “Is sociological consciousness applicable to occupational therapy?” Wilson’s method of concept analysis is used to understand this topic and its practical applications to occupational therapy. Using the Wilson method of analysis to break down the components of this concept, compare it to similar and contrary cases, and explore its social context, the findings suggest that sociological consciousness is relevant to occupational therapy and warrants inclusion in practice, research, curriculum, and continuing education. Sociological consciousness adds depth to clinical reasoning and promotes critical thinking and reflection on implicit biases which may negatively influence therapeutic interactions with clients.